Comparison of haematology and specific serum biochemistry variables between anaesthetised non- injured and injured southern white rhinoceros (Ceratotherium simum simum) - Steenkamp, Gerhardus (University of Pretoria, 2025)
Dissertation (MSc (Veterinary Sciences))--University of Pretoria, 2018.